2018
DOI: 10.1111/trf.14656
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of immunoglobulin prophylaxis in reducing clinical complications of hematopoietic stem cell transplantation: a systematic review and meta‐analysis

Abstract: Immunoglobulin prophylaxis did not have a significant effect on survival. Positive clinical effects were shown for acute GVHD and CMV disease and negative effects against VOD and disease relapse. No studies examined the effect of immunoglobulin treatment in hypogammaglobulinemic patients despite current guidelines, warranting further studies in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
0
18
1
2
Order By: Relevance
“…Intravenous immunoglobulins (IV-Ig) have been proposed as potentially useful either in prophylaxis or in the pre-emptive setting against CMV. Even though some recently data in the pediatric population showed that IV-Ig significantly reduced the incidence of CMV infections,16 and a recently published meta-analysis showed that the prophylactic use of IV-Ig reduced CMV disease,17 the results of historical meta-analysis did not lead to similar conclusions,18 and currently the routinely use of IV-Ig for CMV prophylaxis is not recommended 1922. Anti-CMV Ig (Megalotect) is a specific Ig, which inhibits the entrance of CMV in the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous immunoglobulins (IV-Ig) have been proposed as potentially useful either in prophylaxis or in the pre-emptive setting against CMV. Even though some recently data in the pediatric population showed that IV-Ig significantly reduced the incidence of CMV infections,16 and a recently published meta-analysis showed that the prophylactic use of IV-Ig reduced CMV disease,17 the results of historical meta-analysis did not lead to similar conclusions,18 and currently the routinely use of IV-Ig for CMV prophylaxis is not recommended 1922. Anti-CMV Ig (Megalotect) is a specific Ig, which inhibits the entrance of CMV in the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Amongs the two remaining studies, Steinmuller et al 1989 reported mean rejections per patient of 0.5 and 0.8 at 6 months in the intervention group and the control group, respectively; the corresponding standard deviations were not provided . Vu et al 2015 reported 10% acute rejection in 20 allografts at 4.2 ± 3.5 months after IVIG treatment for BK nephropathy …”
Section: Resultsmentioning
confidence: 99%
“…Note that all the included studies for this review used polyvalent IG, not CMVIG that contains higher concentration of CMV specific IgG antibody. CMVIG had been studied in hematopoietic stem cell transplant recipients with mixed results . Therefore, it is not used in current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…ВВИГ при ТГСК выступает как профилактическое и средство лечения инфекционных осложнений, а также как иммуномодулирующее средство лечения острой реакции трансплантат против хозяина (РТПХ). Именно снижение риска РТПХ и цитомегаловирусной инфекции, особенно при гипогаммаглобулинэмии (IgG < 4,0 г/л) является основным благоприятным терапевтическим эффектом применения ВВИГ в дозе от 0,6 до 5 г/кг веса и более при ТГСК [14]. В 2000-х годах ВВИГ оправдывал возлагаемые надежды (степень доказательности Ib) и был рекомендован к широкому применению при аллогенной ТГСК.…”
Section: другие хорошо известные синдромы с иммунодефицитомunclassified
“…Побочные реакции замедленного типа -это тромбозы, неврологические расстройства, почечная недостаточность, гематологические расстройства (гемолитические реакции, нейтропению), нарушение электролитного баланса, инфекции [2,14,38]. Они встречаются менее чем у 1% пациентов, получавших ВВИГ.…”
Section: частотаunclassified